World cultures and geography - Milson, Andrew J.; Altoff, Peggy; Bockenhauer, Mark H.; Smith, Janet; Smith, Michael William; Moore, David W. (GEO, 2013)
The geographer's toolbox -- Physical & human geography -- Europe geography & history -- Europe today -- Russia & the Eurasian republics geography & history -- Russia & the Eurasian republics today -- Sub-Saharan Africa geography & history -- Sub-Saharan Africa today -- Southwest Asia & North Africa geography & history -- Southwest Asia & North Africa today -- South Asia geography & history -- South Asia today -- East Asia geography & history -- East Asia today -- Southeast Asia geography & history -- Southeast Asia today -- Australia, the Pacific Realm & Antarctica geography & history -- Australia, the Pacific Realm & Antarctica today.